Unveiling the Synergistic Multi-Target Antidiabetic Mechanism of Indonesian Scientific Jamu Formulation: A Computational Study - Andri Prasetiyo; Teguh Sugiarto; Esti Mulatsari; Esti Mumpuni; Vandrico Junky; Fadhiil Muhammad Dzaki Adipura; Claudya Fransiska Pratamauli Nainggolan (Biology, Medicine, & Natural Product Chemistry, 2026)
This study aimed to evaluate the multi-target antidiabetic potential of bioactive compounds within the Indonesian Scientific Jamu formulation (consisting of Andrographis paniculata, Curcuma xanthorrhiza, Cinnamomum burmannii, and Syzygium polyanthum) via an in silico approach targeting PPAR-gamma, DPP-4, AKR1C3, and SGLT2. Molecular docking simulations were performed to screen 238 bioactive compounds using Molegro Virtual Docker to predict binding affinities, while ADMET properties were analyzed using pkCSM. The simulation revealed that Cinnamoside, Procyanidin B2, Bisandrographolide B, and Gemin D exhibited the lowest energy on their respective targets. Significantly, 2,6-Di-O-galloyl-beta-D-glucose emerged as a superior multi-target compound, consistently outperforming standard drugs (Pioglitazone, Teneligliptin, Glimepiride, and Empagliflozin) against all four receptors. It was concluded that the formulation contained potent compounds acting through a synergistic multi-target mechanism, specifically 2,6-Di-O-galloyl-?-D-glucose, providing a molecular rationale for the formulation’s clinical efficacy.